Oral mRNA Vaccines Against Infectious Diseases- A Bacterial Perspective [Invited] - Jawalagatti, Vijayakumar; Kirthika, Perumalraja; Lee, John Hwa (Frontiers in Immunology, 2022)
The mRNA vaccines from Pfizer/BioNTech and Moderna were granted emergency approval in record time in the history of vaccinology and played an instrumental role in limiting the pandemic caused by SARS-CoV-2. The success of these vaccines resulted from over 3 decades of research from many scientists. However, the development of orally administrable mRNA vaccine development is surprisingly underexplored. Our group specializing in Salmonella-based vaccines explored the possibility of oral mRNA vaccine development. Oral delivery was made possible by the exploitation of the Semliki Forest viral replicon and Salmonella vehicle for transgene amplification and gene delivery, respectively. Herein we highlight the prospect of developing oral replicon-based mRNA vaccines against infectious diseases based on our recent primary studies on SARS-CoV-2. Further, we discuss the potential advantages and limitations of bacterial gene delivery.